Tunable nanomechanical performance regimes in ceramic nanowires. (10th September 2019) - Maksud, Mahjabin; Barua, Mathius; Shikder, Md Ruhul Amin; Byles, Bryan W; Pomerantseva, Ekaterina; Subramanian, Arunkumar
Abstract: At the macroscopic size regime, ceramic materials exhibit brittle fracture and catastrophic failure when they are subjected to mechanical loads that exceed their characteristic strength. In this report, we present recoverable plasticity in alpha-phase, potassium stabilized manganese dioxide nanowire ( α -K0.13 MnO2 NW) crystals when they are subjected to atomic force microscopy (AFM) based three-point bending tests at very low loading rates. The force-deflection curves and AFM scans obtained from these measurements reveal yielding and extended plasticity in the NWs during the loading process, while the large plastic deformation is recovered spontaneously during the unloading process. However, the same material system exhibits failure via fracture at substantially higher strengths when it is subjected to bending tests at nearly an order of magnitude higher loading rates. These results highlight an important new pathway to controllably tune the nanomechanical performance of these technologically important nanoceramics for application-specific needs: either achieve self-reversible and ultra-large plasticity, or achieve substantially higher fracture strengths that approach the intrinsic limits of the material system.